Analisis Novel "Tenggelamnya Kapal Van Der Wijck" Karya Hamka Menggunakan Pendekatan Psikologi - Nita Nurhayati; Nurfazria Legiawati; De San San Nurhayati; Jelita Maulida Nurhamidah; Khopipah Alfilani; Ifah Afivah; Via Anggita; Muhammad Hanif Hukama (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2024)
This research analyzes the novel "Tenggelamnya Kapal Van Der Wijck" by Hamka using a literary psychology approach, specifically using the personality structure according to Sigmund Freud, namely Id, Ego and Superego. The research method used is an explanatory qualitative approach using data from the novel. Data collection techniques were carried out through skimming and notation to quote quotes that were relevant to the characters and conflicts in the novel. Content and discourse analysis is used to identify the main themes, conflicts and character development in the novel. The results of the analysis show the psychological conflict experienced by the main character, Zainuddin, in his interactions with his environment, as well as a deep inner conflict due to love that does not reach Hayati. This research provides a comprehensive understanding of the characters and dynamics in the novel. Thus, this research can contribute to further understanding of literary and psychological works, as well as their relevance in understanding the human condition in everyday life.